2022
DOI: 10.4103/sjmms.sjmms_654_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Attention Deficit Hyperactivity Disorder among College Students in Jeddah, Saudi Arabia

Abstract: Background: Childhood attention deficit hyperactivity disorder (ADHD) is commonly diagnosed in Saudi Arabia, but there is negligible evidence regarding adult ADHD in college students. Objective: To determine the prevalence and correlates of ADHD among undergraduates at King Abdulaziz University, Jeddah, Saudi Arabia. Methods: In this cross-sectional study, 2280 undergraduate students from 11 colleges at King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In comparison to recent Saudi studies, all 3 studies showed a lower prevalence rate than our study. 16 - 18 A cross-sectional study carried out in 2020 examined 1177 medical students from 3 medical schools in Riyadh, Saudi Arabia. The study found that only 39 (3.31%) students were diagnosed with ADHD and were using stimulants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to recent Saudi studies, all 3 studies showed a lower prevalence rate than our study. 16 - 18 A cross-sectional study carried out in 2020 examined 1177 medical students from 3 medical schools in Riyadh, Saudi Arabia. The study found that only 39 (3.31%) students were diagnosed with ADHD and were using stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the 2 Riyadh studies, only one cross-sectional study concerning this matter was carried out in Jeddah, Saudi Arabia in 2022. 16 The study included 2,059 students from 11 colleges at King Abdulaziz University, Jeddah, Saudi Arabia. Along with adult ADHD Self-Report Scale it was stated that 11.9% of the students were most likely to have adult ADHD, and out of the total sample, only 6.5% were diagnosed with ADHD during childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, others have reported lower rates, for example locally in the KSA, and a prevalence of 10.9% and 11.9% was both reported in Riyadh and Jeddah, respectively. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Only two studies based on single institutions have looked at ADHD in college students in general reporting rates between 10% and 12%. 16 , 17 The King Salman Centre for Disability Research published in its Saudi national mental health report in 2019 a prevalence of 8% among the 4004 adults aged between 15 and 65 years old. 18 In the same report, the authors recommended that research specific to youth and young adults at schools and universities is needed in order to highlight the status of mental health in this vital specific age group.…”
Section: Introductionmentioning
confidence: 99%